Basic Concepts in Understanding Recovery of Function in Vestibular Reflex Networks during Vestibular Compensation - Peusner, Kenna (Frontiers in Neurology, 2012)
Unilateral peripheral vestibular lesions produce a syndrome of oculomotor and postural deficits with the symptoms at rest, the static symptoms, partially or completely normalizing shortly after the lesion due to a process known as vestibular compensation. The symptoms are thought to result from changes in the activity of vestibular sensorimotor reflexes. Since the vestibular nuclei must be intact for recovery to occur, many investigations have focused on studying these neurons after lesions. At present, the neuronal plasticity underlying early recovery from the static symptoms is not fully understood. Here we propose that knowledge of the reflex identity and input–output connections of the recorded neurons is essential to link the responses to animal behavior. We further propose that the cellular mechanisms underlying vestibular compensation can be sorted out by characterizing the synaptic responses and time course for change in morphologically defined subsets of vestibular reflex projection neurons. Accordingly, this review focuses on the perspective gained by performing electrophysiological and immunolabeling studies on a specific subset of morphologically defined, glutamatergic vestibular reflex projection neurons, the principal cells of the chick tangential nucleus. Reference is made to pertinent findings from other studies on vestibular nuclei neurons, but no comprehensive review of the literature is intended since broad reviews already exist. From recording excitatory and inhibitory spontaneous synaptic activity in principal cells, we find that the rebalancing of excitatory synaptic drive bilaterally is essential for vestibular compensation to proceed. This work is important for it defines for the first time the excitatory and inhibitory nature of the changing synaptic inputs and the time course for changes in a morphologically defined subset of vestibular reflex projection neurons during early stages of vestibular compensation.